Effects of progestin-only contraceptives on the endometrium. Issue 10 (2nd October 2020) - Bastianelli, Carlo; Farris, Manuela; Bruni, Vincenzina; Rosato, Elena; Brosens, Ivo; Benagiano, Giuseppe
ABSTRACT: Introduction: The contraceptive activity of synthetic progestins is mediated through three basic mechanisms: (a) An anti-gonadotrophic action leading to the inhibition of ovulation; (b) Changes in cervical mucus characteristics that inhibit sperm penetration and (c) desynchronization of the endometrial picture necessary for implantation. Areas covered: Mechanisms involved in the progestin-induced endometrium desynchronization are individually reviewed for each of the routes of administration and, whenever possible, by individual members of the various families of synthetic progestin derivatives. Expert opinion: For contraceptive purposes, progestins are today administered through several routes: orally, as injections, subdermally and via the vagina or the uterine cavity. Given this variety of modalities, their effects may differ, depending on the route of administration, concentration reached at the level of the endometrium and the duration of use. These are characterized by inactivation of the endometrium. Progestin-only contraception provides a safe and effective control of fertility regulation, although, they are associated with the problem of endometrial break through bleeding that may lead to discontinuation. Unfortunately, in spite of a major research effort over two decades, there is not, as yet, an established long-term intervention available to manage bleeding irregularities, making mandatory a deeper understanding of the mechanisms involved is required.